New views on the geology of the Bachav-Borzhav subcover of the Duklyan-Monthern cover - Pavlyuk, Myroslav; Shlapinsky, Volodymyr; Savchak, Olesya; Ternavsky, Myroslav (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Statement of the general problem. The article considers the situation that has developed in the Bachava-Borzhav sub-nave of the Duklja-Chornohora nappe, due to the previously undetermined nature of the relationship between the deposits of the Lower Cretaceous Shipotskaya suite with the Bachava sandy stratum of the Upper Cretaceous age.Research materials and methods.To substantiate the absence of the Upper Cretaceous Yalovets'ka suite in the Bachava-Borzhav subcap due to erosion or lithological-facies replacement. The article applies a comprehensive analysis of geological research in the areas of distribution of the Bachava suite.Presentation of the mail research material. The article considers the situation that has developed in the Bachava-Borzhavsky sub-nave of the Duklja-Chornohorska nappe, due to the previously undetermined nature of the relationship between the deposits of the Lower Cretaceous Shipotskaya suite with the Bachava sandy stratum of the Upper Cretaceous age. The Yalovetskaya suite, which should be located between them, is absent. Its absence can be explained by the presence of local erosion or facial replacement of the clayey Yalovetskaya suite as a whole by the sandy Bachava suite. Evidence that allows us to lean towards the idea of facial replacement was obtained by analyzing materials from geological surveys of past years. They consist in the absence of signs that would indicate erosion of the Yalovetskaya stratum (basal conglomerates, angular unconformity). Such replacement has been traced in the same-age deposits in the neighboring Krasnoshora-Hoverla sub-nave, located to the north. There, in the basins of the Chorna Tysa rivers (in the area of the village of Yasinya), the upper part of the thin, undissected Yalovetsya suite is replaced by the sandy Montenegro suite of the Upper Cretaceous (Senonian) stratigraphic range. Lithological replacement of variegated units on sandstone is also noted in the basins of the Mala Shopurka, Seredya Rika and Kosivska rivers. In some areas of the Burkut cover, located further south, almost complete replacement of the clayey Yalovetsya suite by the sandy Burkutsya suite of the Upper Cretaceous age has been recorded. In the neighboring territory of Poland, in the Silesian tectonic unit, the variegated layer, an analogue of our Yalovetsya suite, is lithologically replaced by the same-age Godul sandstones. The fact of this lithological replacement also in the area of the Bachava-Borzhavka subcover allowed us to change the previous interpretation of its geological structureConclusions. Thus, most of the above facts indicate that the absence of the Yalovetskie suite in the Borzhavs segment is explained by its facial replacement by sandy flysch, and in the Bachavskie it is present only in places. The Shipotskie suite of the Lower Cretaceous stratigraphically contacts the transitional thickness of the Upper Cretaceous. The fact of this replacement and the stratigraphically normal contact of the Shipotskie and transitional layers allowed us to change the previous interpretation of the geological structure of the Bachavskie-Borzhavskie sub-roof.